EVALUATION OF SAND EROSION IN OPEN-HOLE STANDALONE SAND SCREEN COMPLETION USING NUMERICAL SIMULATION - SALEH ALGHURABI, AHMED MOHAMMED AHMED (2021)
During oil and/or gas production from unconsolidated sandstone reservoirs, the flow may vary greatly, depending on the reservoir environment. Standalone Screen (SAS) in open-hole completion can provide a highly reliable sand control completion. SAS, however, may also be subject to erosion due to sand impingement and passage through screen apertures. The key objective of this work is to determine the point on the SAS surface where erosion rate is critical and to evaluate the uncertainties in erosion predictions of SAS open-hole completion utilizing numerical simulation (ANSYS fluent software). The geometry model designed in this work is a simplified section of the metal mesh screen (basic type), whereby the aperture size is 200 μm.